Chemical constituents from Valeriana jatamansi. (February 2021) - Wang, Rujing; Shi, Sanjun; Tan, Yuzhu; Yao, Lincai; Zhu, Lixia
Abstract: Phytochemical study of Valeriana jatamansi Jones afforded 45 compounds, including twenty-three iridoids (1 –23 ), five sesquiterpenes (24 –28 ), three steroids (29 –31 ) and fourteen lignins (32 –45 ). The structures of these compounds were assigned by detailed interpretation of spectroscopic data (1D and 2D NMR, HRESIMS) and comparisons with the published data. This is the first report of isolation of compounds (1 –6, 10, 21, 25, 41, 43, 44, 45 ) from Valerianaceae, compounds (13, 27, 39) within the genus Valeriana and compound 30 from V. jatamans . The chemotaxonomic data can support the genus Valeriana being accepted as a member of transitional taxa between the family Valerianaceae and Caprifoliaceae . Graphical abstract: Image 1 Highlights: This is the first report of isolation of compounds (1–6, 10, 21, 25, 41, 43, 44, 45) from Valerianaceae, compounds (13, 27, 39) within the genus Valeriana and compound 30 from V. jatamans. The chemotaxonomic data can support the genus Valeriana being accepted as a member of transitional taxa between the family Valerianaceae and Caprifoliaceae . All the isolates were evaluated for cytotoxicity effect.